Hypersensitive C‐reactive protein‐albumin ratio is associated with stroke‐associated pneumonia and early clinical outcomes in patients with acute ischemic stroke. Issue 7 (24th June 2022) - Huang, Lingling; Zhang, Rong; Ji, Jiahui; Long, Fengdan; Wang, Yadong; Lu, Juan; Xu, Ge; Sun, Yaming
Abstract: Objectives: We aimed to explore the association between the baseline hypersensitive C‐reactive protein‐albumin ratio (CAR) and stroke‐associated pneumonia (SAP) during hospitalization and the short‐term prognosis in patients with acute ischemic stroke (AIS). Methods: We enrolled 766 patients with AIS and collected their admission baseline characteristics, including their National Institutes of Health Stroke Scale score, CAR, age, atrial fibrillation, dysphagia, sex, stroke severity (A 2 DS 2 ) score, and other information. The occurrence of SAP within 7 days after stroke, length of hospital stay, and physical condition at discharge were also recorded. The patients' Modified Rankin Scale (mRS) scores and mortality 3 months after AIS were further evaluated at follow‐up. All patients were divided into four groups based on the quartiles of the admission CAR (Q1 <1.3, Q2 1.3–3.7, Q3 3.7–9.3, Q4 ≥9.3). Results: During hospitalization, 92 (11.9%) patients were diagnosed with SAP. The patients with SAP had a higher CAR than the non‐SAP patients ( p < .001). In the multivariate‐adjusted model, the patients in the Q3 and Q4 groups had a higher SAP risk (aOR was 5.21 and 17.72, p ‐trend < .001) than those in the lowest quartile. The area under the curve for the CAR's ability to predict SAP was 0.810 in the receiver operating characteristic curve analysis and had a similar predictive efficacy as the A 2 DS 2 score ( p < .05). The length of stay in the SAP group was almost the same as that in the non‐SAP group, but the clinical outcomes were worse at discharge and at the 3‐month follow‐up in the SAP group. In addition, the patients in the higher CAR quartiles at admission were more likely to have poorer clinical outcomes. Conclusions: Patients with AIS with a high CAR at admission are more likely to develop SAP during hospitalization and have poor short‐term clinical outcomes. These findings might help to timely identify patients at high risk of SAP and provide a basis for further research on prophylactic antibiotic therapy.